2020
DOI: 10.3389/fcell.2020.591408
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus pentosus Increases the Abundance of Akkermansia and Affects the Serum Metabolome to Alleviate DSS-Induced Colitis in a Murine Model

Abstract: Lactobacillus pentosus has the beneficial function of regulating the host's immune system and plays an indispensable role in intestinal health. The purpose of this study was to investigate the specific mechanism by which L. pentosus relieves dextran sulfate sodium (DSS) induced ulcerative colon inflammation. We randomly divided 24 mice into three groups, which were administered either a basic diet, drinking water with 2.5% DSS (DSS), or drinking water with 2.5% DSS and intragastric administration of L. pentosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…In line with previous research, the relative abundance of Akkermansia genus from Verrucomicrobia phylum decreased signi cantly and even disappeared completely in SBS rats [2]. Akkermansia is a newly discovered star probiotics, which has a variety of bene cial biological functions, such as anti-tumor effect, intestinal mucosal barrier protection, and alleviating colonic in ammation [30][31][32]. Yu Xu and colleagues summarized that Akkermansia could protect the intestinal mucosal barrier and inhibit the translocation of intestinal ora, therefore reducing the level of LPS in circulation and thus inhibiting the in ammatory response.…”
Section: Discussionsupporting
confidence: 80%
“…In line with previous research, the relative abundance of Akkermansia genus from Verrucomicrobia phylum decreased signi cantly and even disappeared completely in SBS rats [2]. Akkermansia is a newly discovered star probiotics, which has a variety of bene cial biological functions, such as anti-tumor effect, intestinal mucosal barrier protection, and alleviating colonic in ammation [30][31][32]. Yu Xu and colleagues summarized that Akkermansia could protect the intestinal mucosal barrier and inhibit the translocation of intestinal ora, therefore reducing the level of LPS in circulation and thus inhibiting the in ammatory response.…”
Section: Discussionsupporting
confidence: 80%
“…Li et al found the central role of alternative M2 skewing of miR-155 in colitis and suggested that macrophages might be the main target of treatment ( Li et al, 2018 ). The Grb2-associated binding protein 2 (Gab2), which plays a role in regulating the activation of macrophages and T cells, and Grb2-associated binding protein 3 (Gab3), which is highly expressed in some immune cell types, redundantly regulate the activation of macrophages and CD8 + T cells to inhibit colitis ( Uno et al, 2010 ; Bezman et al, 2012 ; Best et al, 2013 ; Festuccia et al, 2014 ; Kaneda et al, 2016 ; Wang et al, 2019 ; Ma et al, 2020b ). Human catestatin (hCT), which has immunomodulatory properties, can reduce the severity of inflammatory recurrence by regulating M1 macrophages and releasing pro-inflammatory cytokines ( Zhang et al, 2009 ; Rabbi et al, 2017 ).…”
Section: Macrophages In the Intestinal Mucosa During Inflammationmentioning
confidence: 99%
“…In line with previous research, the relative abundance of Akkermansia genus from Verrucomicrobia phylum decreased significantly and even disappeared completely in SBS rats [ 2 ]. Akkermansia is a newly discovered star probiotics, which has a variety of beneficial biological functions, such as anti-tumor effect, intestinal mucosal barrier protection, and alleviating colonic inflammation [ 30 32 ]. Yu Xu and colleagues summarized that Akkermansia could protect the intestinal mucosal barrier and inhibit the translocation of intestinal flora, therefore reducing the level of LPS in circulation and thus inhibiting the inflammatory response [ 33 ].…”
Section: Discussionmentioning
confidence: 99%